Aspiracje edukacyjne rodziców i dzieci a osiągnięcia szkolne - Kozłowski, Waldemar; Matczak, Ewa (Wydawnictwo Naukowe UAM, 2018)
Numerous studies have found an association of educational aspirations of parents and children with their school achievement. The study verifies these relationships for about 5,000 people, a representative sample of parents and their children-primary school students. Three aspects of aspirations were taken into account: the maximum (desired), the feasible (expected) and the lowest acceptable. Expected aspirations of parents are mostly related to the achievements of children; students’ achievements are associated with both their feasible and maximum aspirations. There was a significant relationship between aspirations of parents and children and a strong correlation between parental aspirations and their level of education.
Educational Aspirations of Parents and Children and School Achievement
Keywords: educational aspirations; parents; children; educational achievement